1996
DOI: 10.1046/j.1471-4159.1996.67010352.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Repeated Systemic Amphetamine Administration: Effects on Extracellular Glutamate, Aspartate, and Serine Levels in Rat Ventral Tegmental Area and Nucleus Accumbens

Abstract: Recent work indicates an important role for excitatory amino acids in behavioral sensitization to amphetamine. We therefore examined, using in vivo microdialysis in awake rats, the effects of amphetamine on efflux of glutamate, aspartate, and serine in the ventral tegmental area and nucleus accumbens, brain regions important for the initiation and expression of amphetamine sensitization, respectively. Water-pretreated and amphetaminepretreated rats were compared to determine if sensitization altered such effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
114
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(129 citation statements)
references
References 55 publications
14
114
1
Order By: Relevance
“…aCSF was then perfused immediately at a rate of 1.0 ml/min through both probes. This procedure of initiating the experiment immediately following probe insertion was utilized because we and others have found that brain injuryderived, that is, non-neuronal, levels of glutamate are higher 18-24 h following probe implantation (Obrenovitch et al, 1993;Xue et al, 1996). Samples were collected every 30 min for immediate determination of DA in the mPFC and subsequent determination of glutamate in the VTA.…”
Section: Methodsmentioning
confidence: 99%
“…aCSF was then perfused immediately at a rate of 1.0 ml/min through both probes. This procedure of initiating the experiment immediately following probe insertion was utilized because we and others have found that brain injuryderived, that is, non-neuronal, levels of glutamate are higher 18-24 h following probe implantation (Obrenovitch et al, 1993;Xue et al, 1996). Samples were collected every 30 min for immediate determination of DA in the mPFC and subsequent determination of glutamate in the VTA.…”
Section: Methodsmentioning
confidence: 99%
“…While methamphetamine's effects upon the monoaminergic systems have received considerable experimental attention [for reviews, [264][265][266][267][268][269][270], less is known regarding the regulation of corticoaccumbens glutamate and glutamate receptor expression by amphetamine and methylated analogs. Acute administration of amphetamines is reported to produce either no change or a delayed rise in extracellular glutamate levels within striatal regions [59][60][61][62]271,272], while an acute injection of methamphetamine, but not amphetamine, elevates PFC glutamate levels [271]. Whereas repeated cocaine administration produces robust drug-induced glutamate sensitization within the NAC [e.g., 31,35,47,57], repeated dosing with non-toxic regimens of amphetamine or methamphetamine elicits little effect upon the capacity of these drugs to alter glutamate levels within the corticoaccumbens pathway [61,272].…”
Section: Homers and Methamphetaminementioning
confidence: 99%
“…Acute administration of amphetamines is reported to produce either no change or a delayed rise in extracellular glutamate levels within striatal regions [59][60][61][62]271,272], while an acute injection of methamphetamine, but not amphetamine, elevates PFC glutamate levels [271]. Whereas repeated cocaine administration produces robust drug-induced glutamate sensitization within the NAC [e.g., 31,35,47,57], repeated dosing with non-toxic regimens of amphetamine or methamphetamine elicits little effect upon the capacity of these drugs to alter glutamate levels within the corticoaccumbens pathway [61,272]. In contrast, repeated high dose amphetamine or methamphetamine regimens that induce dopamine neurotoxicity produce an increase in glutamate content within the PFC [273], a delayed increase in dorsal and ventral striatal glutamate levels [60,[274][275][276][277] and enhance potassium-stimulated, but not methamphetaminestimulated, glutamate release within the PFC [277].…”
Section: Homers and Methamphetaminementioning
confidence: 99%
“…Psychostimulants promote glutamate efflux in the VTA (Kalivas and Duffy, 1995;Xue et al, 1996;Wolf and Xue, 1998), due to efflux from glutamate transporters and cystine-glutamate exchangers (Wolf and Xue 1999;Baker et al, 2002Baker et al, , 2003. In principle, this rise in extracellular glutamate could contribute to the development of LTP, but studies indicate that this rise does not begin until 2 h after psychostimulant exposure (Xue et al, 1996;Wolf and Xue, 1998). Since we observe increased AMPAR/NMDAR ratios within this time period, the rise in extracellular glutamate may not be required for these early synaptic changes.…”
Section: Changes In Ampar/nmdar Ratio Are Rapidmentioning
confidence: 99%